1577. Real-World, Multicenter Experience with Eravacycline for Various Infections. (31st December 2020) - Alosaimy, Sara; Lagnf, Abdalhamid M; Molina, Kyle; King, Madeline; Pullinger, Benjamin; Tart, Serina; Jones, Bruce M; Claeys, Kimberly C; Truong, James; Andrade, Justin A; Biagi, Mark; Pierce, Michael; et al.
Abstract: Background: Eravacycline (ERV) is Food and Drug Administration approved in patients for the treatment of adults complicated intra-abdominal infections in 2018. Real-world data regarding the indications for ERV use are is limited. We evaluated the clinical/safety outcomes of patients treated with ERV in FDA and non-FDA approved indications. Methods: Multicenter, retrospective, observational study from September 2018 to June 2020. Adult patients treated with ERV for ³ 72 hours were included. The primary outcome was 30-day survival. Secondary outcomes included a lack of 30-day infection-recurrence, resolution of signs/symptoms of infection and safety. All outcomes were measured from ERV start date. Results: Overall, 108 patients were included from 12 geographically-distinct medical centers across the United States. The median(IQR) age was 60(52-67) years and 60% were male. Median(IQR) APACHE II and Charlson Comorbidity scores were 15(11-21) and 3 (2-6), respectively. The most common sources of infection were intra-abdominal (32%), and respiratory (24%). Common pathogens included Acinetobacter baumannii (19%), Klebsiella pneumoniae and Enterococcus faecium (16%). Infectious diseases consultation was obtained in 98%, and surgical interventions in 51% of cases. Patients often received active therapy prior to ERV(40%). Median(IQR) ERV therapy duration was 7.7(4.4-14.0) days. Among cases with documented cultures, ERV was initiated within a median(IQR) of 4.8(2.5-9.9) days. Combination therapy ³ 48 hours was given in 45%. The primary endpoint was achieved in 79%(85/108). Of patients who died(n=23), 57% were on monotherapy, 39% were critically ill, 39% had intra-abdominal as a source, and 30% had positive blood cultures. For secondary outcomes, 94%(102/108) lacked 30-day infection-recurrence and 74%(80/108) resolved signs/symptoms of infection. ERV was selected primarily for consolidation of the regimen(40%). Eight patients experienced a probable ERV-related adverse event, mainly gastrointestinal(87.5%) and none experienced clostridium difficile. Conclusion: 30-day survival was achieved in the majority of patients treated with ERV. Studies with longer follow-up are required to confirm these findings. Disclosures: Madeline King, PharmD, Tetraphase (Speaker's Bureau) Bruce M. Jones, PharmD, BCPS, ALK-Abello (Research Grant or Support)Allergan/Abbvie (Speaker's Bureau) Michael J. Rybak, PharmD, MPH, PhD, Paratek (Grant/Research Support)